Genotype and environment interaction analysis for yield stability and resistance to aspergillus flavus in of groundnut (Arachis Hypogaeal.)Advanced lines (Bangladesh Journal of Botany, 2025)
This study intended to assess advanced groundnut linesobtained from the cross between the Spanish bunch genotype,GPBD 4, which is resistant to rust and late leaf spot but highly susceptible to Aspergillusinfection and ICGV 2207, which istolerant to Aspergillusinfection. 198 advanced lines (F4-F6) along with their parents were evaluated for over three consecutive years (2019 to 2021) in Dharwad, Bagalkot and Belagavicomprisingfive distinct environments. Multivariate stability analysis was conducted to identify high yieldingand stablelines with resistance to Aspergillusflavusinfection. The results  revealed highly significant variations(P